Stages and organization of state strategic development planning in the field of medical tourism - Gushcha, Taras (Public Policy and Accounting, 2024)
In view of globalization, medical tourism has become a special and multifaceted sphere of international services. It not only combines medical care with travel, but also influences the social, economic, infrastructural, international and tourism policies of different countries. Its uniqueness lies in the variety of reasons that encourage people to go abroad for treatment and recovery, as well as in the differences in the ways of organizing such trips. Developing a clear strategy is the key to reforming the branches of public administration. At the same time, it is important to determine strategic goals, objectives and success criteria that will become the basis for implementing public policy. In the context of modern internal and external challenges, there is an urgent need to form a holistic vision of the development of medical tourism in Ukraine. This will allow for the necessary reforms in the healthcare system, the hospitality industry, infrastructure, the tourist services market and other related industries. Having analyzed the scientific literature, it should be noted that the development of public administration involves a combination of methods of direct and indirect influence, as well as the division of methods into general and special. Taking into account the peculiarities of state strategic planning and considering medical tourism as an important area of ​​state policy, the author identified key tools for implementing its development strategy: legal (development and adoption of regulatory legal acts on the development of medical tourism in general and its components in particular); economic (formation of instruments for financial support of medical tourism and entities implementing medical tourism services); organizational (modernization of the subject structure of state administration of medical tourism); informational (providing informational support and popularization of the development of medical tourism from the perspective of both the country of departure and the country of destination). These tools were laid down as the basis of a comprehensive mechanism for implementing the strategy for the development of medical tourism, which will ensure the coordination of medical, tourist, economic, legal, social and international components of the object under study. As a result of the study, it should be noted that for the successful implementation of the medical tourism development strategy, a multi-component approach is necessary, covering various areas and instruments of state influence.